Qualifying and specially qualifying features of the illegal removal of human organs or tissues - Гринчак, Сергій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article analyzes the illegal removal of organs or tissue from a person who is helpless or in material orother dependence on the perpetrator.